2022
DOI: 10.1097/pec.0000000000002863
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound for the Diagnosis of Pediatric Testicular Torsion

Abstract: Objectives: Acute testicular torsion is a surgical emergency that warrants prompt treatment. The diagnosis is typically confirmed by ultrasonography interpreted by a radiologist (RADUS); however, in this study, we describe the clinical course of 23 patients for whom point-of-care ultrasound (POCUS) was performed by pediatric emergency medicine physicians during the initial assessment for testicular torsion in the pediatric emergency department (PED).Methods: A retrospective case series analysis of patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A recent case series reported results on surgical exploration after only performing POCUS without a comprehensive RADUS. 12 POCUS demonstrated efficiency in the early recognition of TT and there were no false-positive results. Two patients in our study who underwent surgical exploration without RADUS, leading to a shorter EDLOS (113 and 166 hours versus 197 hours) and shorter door-to-surgery time (134 and 163 hours versus 212 hours) compared with that of all patients with TT.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A recent case series reported results on surgical exploration after only performing POCUS without a comprehensive RADUS. 12 POCUS demonstrated efficiency in the early recognition of TT and there were no false-positive results. Two patients in our study who underwent surgical exploration without RADUS, leading to a shorter EDLOS (113 and 166 hours versus 197 hours) and shorter door-to-surgery time (134 and 163 hours versus 212 hours) compared with that of all patients with TT.…”
Section: Discussionmentioning
confidence: 85%
“…3,11 To reduce unnecessary delays in ED, the use of pointof-care ultrasound (POCUS), which can be quickly performed by the ED physician, has been increasing and being investigated recently in the same manner as other pediatric emergencies, including intussusception, acute appendicitis, and infantile hypertrophic pyloric stenosis. [12][13][14][15][16][17] Mori et al reported high sensitivity and specificity for diagnosing TT using POCUS. 13 Koppel et al reported advantages, such as a shortened ED length of stay (EDLOS), when using POCUS as a confirmatory test for surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, in a retrospective case series analysis involving 155 patients, POCUS performed by pediatric emergency physicians reduced the time from admission to orchiopexy by 63 minutes. 13 POCUS can provide good guidance for manual detorsion and increase the success rate of blood flow restoration in the testis. Research using ultrasound guidance during manual detorsion is lacking, especially when performed by emergency physicians.…”
Section: Techniquementioning
confidence: 99%
“…In a review study of 120 patients, POCUS performed by pediatric emergency physicians had a diagnostic accuracy rate of 70% for testicular torsion 12 . In addition, in a retrospective case series analysis involving 155 patients, POCUS performed by pediatric emergency physicians reduced the time from admission to orchiopexy by 63 minutes 13 …”
Section: Review Of the Literaturementioning
confidence: 99%